The Enhancement in Mastery Abilities of Geometric Transformation Formulas Through Play Lucky Card Technique on the Students of Class VIII-2 at SMP Negeri 3 Barru, Indonesia - Muhammad Talha (Journal of Applied Science, Engineering, Technology, and Education, 2021)
The method used in this study was a classroom-based action research that aimed to improve students' mastery of the geometric transformation formulas through the Play Lucky Card technique. This study was conducted in class VIII.2 of SMP Negeri 3 Barru with 23 students. The results achieved after the study was carried out for two cycles were as follows: In the first cycle, there were 40.63% of students who had the ability to master the geometric transformation formulas in the sufficient category. Whereas in the classical results, it was found that the students' average score was 68.06 in the 54.6-64.5 interval or in the sufficient category. In the second cycle, there were 56.25% of students who had the ability to master the mathematical formulas in the high category, 28.13% of students had the ability to master the mathematical formulas in the very high category. From the results of the final evaluation of the second cycle, it was classically found that the students' average score was 76.75 in the 64.6-84.6 interval or in the high category. Based on the results of the final evaluation, the students of class VIII.2 had an absorption amounted to 86.75%, and other data showed that the students of class VIII.2 who scored > 65 (84.38%), were in the high and very high category. Thus, it can be concluded that there was an increase in the ability to master the geometric transformation formulas of class VIII.2 students at SMP Negeri 3 Barru after the implementation of Play Lucky Card technique, there was an increase in motivation and activeness as well as the presence of students following the mathematics learning process. This was reflected in the number (quantity) of students who raised their hands to work on the questions on the blackboard which tended to increase from one meeting to the next. Moreover, almost all students submitted every homework according to predetermined deadlines.